Trimethylamine N-oxide (TMAO): a new attractive target to decrease cardiovascular risk. - Swanepoel, Ione; Roberts, April; Brauns, Chelsea; Chaliha, Devahuti; Papa, Veronica; Palmer, Raymond D; Vaccarezza, Mauro (2021)
Cardiovascular disease (CVD) is one of the greatest disease burdens and takes the lives of many each year. There are many risk factors both modifiable and non-modifiable which contribute to the onset and progression of the disease. Trimethylamine N-oxide (TMAO) in recent years has been found to have a correlation with CVD onset. Those with increased levels of the metabolite have a markedly increased risk of future development of cardiometabolic disorders.This literature review aimed to critique past studies undertaken to find a consensus of the significance of the interrelationship between TMAO and cardiovascular risk. A definite link between TMAO levels and a CVD outcome was found. The majority of the literature stated the relationship with evidence; however, there is still some uncertainty as to why and how the correlation occurs. Further study needs to be done to further dissect and understand the relationship between TMAO and CVD risk.